2007
DOI: 10.1108/17511870710721462
|View full text |Cite
|
Sign up to set email alerts
|

Medical talent management: a model for physician deployment

Abstract: Provides a new use for a well-validated career assessment and planning system. The actual value of this approach should be studied using best-practices in ROI research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…All three dimensions of talent management had a significant relationship with retention rates. The results of this study are also consistent with other conducted studies (Brightman, 2007;Goestjahjanti et Helaly, El-Sayed, 2022). From the same point of view, it has been found that the ability to retain employees in an organization depends on fully developing, understanding and managing their talents (Kravariti et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…All three dimensions of talent management had a significant relationship with retention rates. The results of this study are also consistent with other conducted studies (Brightman, 2007;Goestjahjanti et Helaly, El-Sayed, 2022). From the same point of view, it has been found that the ability to retain employees in an organization depends on fully developing, understanding and managing their talents (Kravariti et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…In response to this challenge, talent management system is used in order to improve and expand quality, fitness, mastery, experience, and culture in nursing workforce (Cowan, Norman, Coopmah, 2005;Douglas, 2013). For more than one decade, talent management system has been applied in the healthcare system which is a good health indicator (Brightman, 2007;Douglas, 2013).…”
Section: Talent Management and Nurses Performancesmentioning
confidence: 99%
“…There are several research studies in the international bibliography supporting the positive effect of T.M. on outflows in the field of health [6][7][8]. A recent overview of T.M.…”
Section: Introductionmentioning
confidence: 99%